System Payment Mu’nah in Gold Pawn Financing Indonesian Syariah Bank, Lumajang S. Parman Branch Office - Nasrifah, Maula; Darma Oktaviana, Shinta (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
Maintenance fee (mu'nah) is a gold pawn maintenance fee that is calculated based on a certain proportion of the estimated collateral pawned by the customer. The purpose of this study was to determine the gold pawn financing mechanism of Bank Syariah Indonesia, Lumajang S. Parman Branch Office and to describe the implementation of the mu'nah payment system of Bank Syariah Indonesia, Lumajang S. Parman Branch Office. The type of research used in this study is a qualitative method with a descriptive approach. Data collection techniques use interviews, observation and documentation, then the data is analyzed by reducing data, presenting data, drawing conclusions. Data validity uses source triangulation techniques. This study concluded: 1) The gold pawn financing mechanism at BSI KCP Lumajang S. Parman has a very easy process with simple terms and conditions, no interest is charged, financing does not contain gharar and is based on sharia law. 2) Implementation of the mu'nah payment system in gold pawn financing, there is collateral in the form of jewelry or gold bars held by BSI and its security and safety are maintained by imposing mu'nah fees (maintenance fees) which are borne by the customer. Customers who take financing below the predetermined estimated value get a mu'nah discount. The determination of the mu'nah fee discount has been automatically systematized when the officer inputs the nominal financing taken by the customer.